Born to be Unequal? An Assessment of the Rights and Status of Hindu Women in Bangladesh (Dhaka University Law Journal, 2025)
This article examines the legal and social status of Hindu women in Bangladesh, with a focus on their rights to property, marriage, guardianship, maintenance and adoption. It also analyses the factors that contribute to their unequal status, such as religious dogmatism, patriarchal norms, social stigma etc. The study draws on a community survey conducted among 743 Hindu respondents, which reveals their perception of inequality and discrimination against Hindu women, as well as their opinions on the potential reforms of Hindu law in Bangladesh. The article argues that Hindu law in Bangladesh is outdated and unfair to women and that it needs to be reformed in line with the Indian reforms or replaced by a uniform family code that ensures equal rights for all citizens regardless of religion. The article also suggests some steps to be taken to ensure equality for Hindu women and improve their legal and social status in Bangladesh.Dhaka University Law Journal, 2024, 35 (1), 113-150